Immobilized Tio2/Activated Carbon Bilayer System For The Removal Of Phenol Via Photocatalytic-Adsorptive Processes - Bahrudin, Noor Nazihah (2012)
Titanium dioxide (TiO2) and activated carbon (AC) had been combined in an immobilized bilayer arrangement on glass plates for the removal of phenol. The immobilized monolayer AC/ENR50/PVC and bilayer TiO2/AC/ENR50/PVC systems have been successfully fabricated via a dip-coating method. The adhesives used in both activated carbon and TiO2 dip-coating solutions were ENR50/PVC blends. The purpose of the fabrication was to photocatalytically remove phenol from aqueous solution as opposed to the conventional suspension method.